(untitled) (International journal of medical sciences, 2026)
Objective: to evaluate the clinical efficacy, safety, and impact on postoperative pain relief of complex ultrasound navigation during brachial plexus block in patients with upper limb injuries and diseases. Materials and Methods: the study included 150 patients (64 men, 86 women; mean age 39.8±16.3 years) who underwent brachial plexus block. The main group (n=100) included patients with injuries, chronic pain syndromes, and postoperative conditions; the control group (n=50) included patients undergoing elective surgeries without nerve damage. The block was performed under the control of ultrasound navigation using gray-scale echography, color Doppler imaging, and compression elastography. Results: The use of ultrasound navigation reduced the block time (8.4±2.1 vs. 15.2±3.8 min, p< 0.05), increased the block success rate (96% vs. 82%), and reduced the need for repeat anesthesia (4% vs. 18%). The frequency of vascular punctures decreased more than threefold. The duration of postoperative analgesia increased to 11.5±2.3 hours. Conclusion: Integrated ultrasound navigation improves the accuracy and safety of brachial plexus block, enhances the quality of pain relief, and reduces the incidence of complications, making it the method of choice for injuries and surgeries on the upper extremities.